Migration of humans fleeing conflict in the Lake Chad region may increase pressures on natural resources in Lake Fitri (Chad): A case study on waterbirds - (:unkn) unknown (My University, 2024)
Sustainable harvest of wildlife is a major food security and conservation issue. In Africa, where wildlife is harvested mainly for subsistence, this remains a challenge. In this study, using waterbirds as model for natural resources, we assessed the sustainability of harvest through fishing bycatch on Lake Fitri (Chad). 2. We estimated the abundance of 24 target taxa through aerial distance sampling over four consecutive years (2018-2021) and in parallel estimated the number of birds harvested through interviews of a sample of 105 out of approximately 5500 fishermen. 3. By modelling their potential excess growth, we found a high risk of overexploitation for four species, including the world-threatened Black Crowned Crane Balearica pavonina, likely due to an influx of fishermen to Lake Fitri fleeing the Boko Haram security crisis. Synthesis and applications: This work is likely the first quantitative approach of bird harvest sustainability in Africa. It should contribute to fill a methodological and an information gap in the strategic planification of several multilateral environmental agreements like the African-Eurasian Waterbird Agreement and the Ramsar Convention. In particular, this work could help implementing adaptive management of natural resources (including birds) in Ramsar site management plans. African wetlands such as Lake Fitri may not be able to provide enough natural resources in the medium term for movements of displaced civilians forced by armed conflict into such biodiversity strongholds.
Keywords: African Research